Penumbuhan Kepedulian Terhadap Lingkungan Dan Aksi Sosial Kepada Anak di Desa Pearung, Kecamatan Paranginan, Kabupaten Humbang Hasundutan - Harisan Boni Firmando (Jurnal Abdi Mas Adzkia, 2022)
The current apprehensive environmental condition is due to the large number of people who do not have the awareness to care about the environment. It takes care from the community so that a beautiful environment can be realized. Various efforts have been made to realize the beauty of the environment, one of which is through service programs that aim to foster public awareness of the environment. This service uses an empowerment perspective with the ABCD (Asset Based Community Development) method to foster environmental awareness, so that the environment in Pearung Village can be sustainable and efficient for the community. This service seeks to empower the community by providing various information about environmental care through counseling, thus opening the community paradigm to maintain environmental cleanliness, save existing resources and plant horticultural crops and carry out persuasive efforts in the form of social action activities such as socializing the 5 M Movement, distributing masks. and distribute books. The results of this service can be seen from the beautiful village area and the increasing public concern for the environment.